THE STUDY OF HEAVY METAL CONCENTRATIONS IN THE RED MUD DEPOSITS AT THE GULF OF CORINTH, USING MULTIVARIATE TECHNIQUES - Iatrou, M.; Papatheodorou, G.; Geraga, M.; Ferentinos, G. (Bulletin of the Geological Society of Greece, 2010)
Detailed geochemical analyses were performed on the recent sedimentary cover (0 – 15 cm) of the northern flank of the Gulf of Corinth, in western Greece. Man-made metalliferous deposits have been formed on the sea-bed of the Gulf due to the discharge of red mud tailings on the shelf of the Antikyra Bay. The metalliferous deposits have been incorporated in the sedimentation regime of the area. A large grid of sediment samples collected from surface and subsurface red mud deposits and the surrounding natural sediments were analysed for Ag, Al, Cd, Co, Cr, Cu, Fe, Hg, Mg, Mn, Ni, Pb, Si, Ti, V, and Zn concentrations, using Atomic Absorption Spectrometry (AAS). Also, Total Organic Carbon and Calcium Carbonateswere determined. Additionally, correlation between heavy metal concentrations and grain-size data was examined. High heavy metal content values were measured on the floor of the Corinth basin, but the highest heavy metal concentrations occur near the discharge site. In subsurface sediments the heavy metal content (Fe, Ni, Cr, Pb, V, Ag, Co, Al, Cd, Ti, Hg) is significantly higher in the red and reddish mud sediments than in the natural mud sediments. The heavy metal content values decrease from top to base within red-mud deposits. Multivariate statistical methods (Cluster and Facto analysis) were applied on the heavy metal composition and grain-size dataset in order to investigate the inter-element relationships as well as the relationships between the geochemical and sedimentological data.